The participation of indigenous peoples in international norm-making in the Arctic - Koivurova, T; Heinämäki, Leena (Polar Record, 2006)
Indigenous peoples regularly regard international law as a very important tool for the advancement of their political goals. This is most likely because in many nation-states their opportunities for influencing political development are rather limited. Even though international law seems to be an important means for indigenous peoples to advance their goals, these peoples should be aware of its inherent limitations. One such shortcoming is that international law seriously restricts indigenous peoples' opportunities to participate in the international law-making processes; that is treaty and customary law. The contention in this article is that the recent norm-making method of soft law provides indigenous peoples with a better opportunity for influential participation than is afforded them by traditional methods. If these peoples are to benefit from this opportunity, however, we must appreciate the revolutionary potential of the concept: a potential that is suffocated if the concept is understood only from the perspective of international law. A good example of indigenous peoples gaining a better standing in inter-govemmental co-operation is the Arctic Council, which based its work on the soft-law approach from the outset. There would seem to be good prospects for adopting the Arctic Council's approach in other regions of the world in order to improve indigenous peoples' international representational status.